PARA ALÉM DA GESTÃO E DO FINANCIAMENTO:A DIMENSÃO INSTITUCIONAL DA CRISE DO SISTEMA ÚNICO DE SAÚDE - Vicente, Bruno Leonardo Brito (2013)
This dissertation studies the SUS. Analyzes the problems and limitations that prevent you from performing so full, which in practice means sometimes precarious conditions, unequal and insufficient actions and health services, in flagrant conflict with the SUS idealized. The first chapter discusses the financial dimension. Most of the literature that seeks to diagnose the reasons for not achieving the promises of SUS focuses on the inadequacy and irregularity of resources for its financing. Then, in the second chapter, it is the managerial dimension. Analyzes the debate about failures and "bottlenecks" in the existing management system, both the administrative structure as the activities provided. In the third chapter, the core of the work is devoted to analyze the institutional dimension of the SUS that, in view of the Brazilian constitutional order rests on federal matters. The thesis is that the solution to the challenges of realizing the SUS spends decisively by addressing the relationship between the Brazilian public health system and our model of federalism